The role of the family in the normalization of the pregnancy at an early age (Encuentros, 2016)
The research on “ Motivations and meanings on cultural character which show in management styles of micro, small and medium enterprises in Boyacá”, wish to make an approach to mental model underlying the management style of micro and small enterprises in the department of Boyacá, particularly in the dimension of motivations and meanings regarding the following categories: family-business relationship, relationship State - enterprise, customer, employee, partnership, globalization and long term. Through a qualitative research which implicated 30 micro and small enterprises, it was found that the meanings expressed on these seven variables significantly influence the model, and consequently, the reading that the manager does about the phenomena of the enterprise, saves intimate relationship with their meanings about cited variables.Keywords: Motivations and meanings, management style, micro and small enterprises, Mental model, culture.